Análise genética e morfométrica da estrutura populacional do camarão branco Litopenaeus schmitti (Decapoda , Crustacea) na costa do Rio Grande do Norte, Brasil: uma abordagem em fina escala - Luvesuto, Eloize (2006)
The natural populations of the white shrimp Litopenaeus schmitti are being threatened by intensive fishing, habitat destruction and introduction of exotic culture species. This species presents characteristics related to its distribution and life cycle that may lead to the fine-scale structuring of its populations. The results obtained in the present work by biometric and microsatellite analysis indicated the existence of genetic and morphological structure between three populations sampled off the coast of the State of Rio Grande do Norte. This structuring was more pronounced for females than males, observing the significant differentiation between Diogo Lopes x Touros and Diogo Lopes x Baía Formosa. The factors responsible for this differentiation seem to be related to the habitat and life cycle of the shrimp and the ocean currents. No population was in the Hardy- Weinberg equilibrium, probably due to the significant heterozygote deficit (FIS=0,212, p<0,05). The assignment tests indicated a larger inflow of migrants in the Baía Formosa Diogo Lopes direction, a probable result of the Brazilian Northern Current and the Brazilian North Undercurrent. When the allelic richness and number of private alleles were compared, it was seen that Diogo Lopes and Touros presented similar and significantly larger values than those of Baía Formosa, corroborating the situation of the estuaries that influences each of these populations. The Mantel test did not show isolation by distance, indicating that the populational structure found is due to genetic and genotypic differences. The results obtained in the present work show for the first time that Brazilian shrimp populations may be genetically distinct even with small geographic distances, reinforcing the particular role of estuaries in the maintenance of this genetic diversity.